اللّبس، وأثره في التصحيح اللغوي - سعيد, هاوكار عبد الرحمن (Sulaimani Journal for Humanities, 2022)
This research deals with the phenomenon of confusion and its impact on some linguistic issues and linguistic correction. The research presented a theorizing about clarity in speech, and the importance of the recipient in the communication process. He touched on the phenomenon of confusion at the levels of language (phonetic, morphological and syntactic) and came up with one or more examples for each of these levels. Then the research indicated the effect of this phenomenon on linguistic correction, and the weighting of some linguistic issues that formed a difference between linguists - ancient and modern -Based on this phenomenon, the research suggests that vocabulary and structures are not more eloquent than others, but to avoid confusion, it is necessary to choose this and leave that.